إدارة الصيانة وانعكاساتها على إدارة الانتاج في الشركات الصناعية " دراسة تطبيقية على الشركات النفطية العاملة في ليبيا" (Al-Farooq Journal of Sciences, 2026)
The problem of this study is the insufficient attention given by top management of industrial projects to maintenance management resulting in low performance level of proactive (protective) and reactive maintenance works.This study acquires its importance from the importance of project it addresses; that is; management of protective and reactive maintenance operations in the companies under study and from its significant role to increase awareness of those who are responsible for maintenance works including engineers and employees of these companies.It is also important as to adopting the requirements of maintenance operations management by applying planning and scheduling to maintenance works and measuring performance level of protective and reactive maintenance works as well as to what extent the companies under study will benefit of the results of this study. The study highlights also the differences of maintenance costs among the companies under study; not to mention to the scientific enriching it will contribute to knowledge and using scientific techniques to apply planning and scheduling and use computer in protective and reactive maintenance works. This study aims to evaluate the status of maintenance management and its concepts in oil companies operating in Libya by investigating this concept and measuring performance standard of maintenance management in the companies under study. The study seeks future results as to securing sufficient operation, carrying out proactive and reactive maintenance operations at least cost and constructing a computer software to use in maintenance works based on the inforınation base "C.M.M.S".The study is based on the following hypotheses:First: Lack of interest by the top management of the companies under study in maintenance management adversely affects productive activity. Such a deficiency is reflected in:A. Allocating more time to maintenance worksB. Increasing of maintenance costs and hence production cost.C. Shortening of life expectancy of equipment and machines.Second: Lack of efficient and skilled personnel required to undertake maintenance works.Third: Lack of a uniform comprehensive system for planning and organizing proactive and reactive maintenance works adversely affects the productive activity of the companies under study.The theoretical part of this study addresses the problem of study, objectives to be met, the status of maintenance management function in the companies under study and its components and techniques and forms of maintenance in oil companies under study. The practical part of the Study includes information collected from a field survey on maintenance operations conducted in the companies under study on a questionnaire developed for this purpose. The said questioner was built on the following axes:First: manpower Second: relation with maintenance management function Third:training in maintenance works Fourth: data related to study Fifth: elements and components related to proactive and reactive maintenance in the companies under study Sixth: maintenance management system in the companies under study.Through data analysis, performance efficiency of maintenance operations in the companies under study was measured, conclusions reached were discussed indicating deficiencies in maintenance works and recommendations, results and proposals for further future studies were presented.